Kiln drying of timber in peninsular Malaysia : a review / Muhamad Faizal Hashim - Hashim, Muhamad Faizal (2000)
Drying process is an important process in wood industry sector. In production of sawn timber, mouldings, furniture production, bridge making an other wood products. This industry also contribute to economic development of the country and also as an export wood based industry in this country. This study reviews the status and development in kiln-dry industry in Peninsular Malaysia.